Case Report: Potential Applications of Using a 3D-Ring CZT SPECT for Lymphoscintigraphic Exploration of Lower Limb Edema - Besse, Hélène; Bailly, Matthieu (Frontiers in Medicine, 2022)
Lymphoscintigraphy is still considered the gold standard imaging modality for diagnosing lymphedema, due to ineffective lymphatic transport resulting in edema and skin damage. However, protocol variability and poor image resolution can make the interpretation challenging. Up to now, 99mTc-labeled colloid lymphatic travel is monitored with dual-head cameras but SPECT has proved its interest. Here, we present the case of a 59-year-old-man with bilateral asymmetric lower limb edema explored using dual-head and new 3D-ring CZT SPECT cameras, confirming bilateral lower limb lymphatic dysfunction. This case report, in line with other recent published reports, promote the use of SPECT/CT in lymphoscintigraphic exploration of lower limb edema. Recognition of the clinicopathologic features of lower limb edema is required to prevent missed diagnosis, such as compressive disease, tumors…, and to better influence management of patients.